Modelling boundary-layer transition on wings operating in ground effect at low Reynolds numbers - Roberts, Luke S.; Finnis, Mark V.; Knowles, Kevin (Sage, 2018)
The transition-sensitive, three-equation k-kL-ω eddy-viscosity closure model was used for simulations of three-dimensional, single-element and multi-element wing configurations operating in close proximity to the ground. The aim of the study was to understand whether the model correctly simulated the transitional phenomena that occurred in the low Reynolds number operating conditions and whether it offered an improvement over the classical fully turbulent k-ω shear stress transport model. This was accomplished by comparing the simulation results to experiments conducted in a 2.7 m × 1.7 m closed-return, three-quarter-open-jet wind tunnel. The model was capable of capturing the presence of a laminar separation bubble on the wing and predicted sectional forces and surface-flow structures generated by the wings in wind tunnel testing to within 2.5% in downforce and 4.1% in drag for a multi-element wing. It was found, however, that the model produced insufficient turbulent kinetic energy during shear-layer reattachment, predicted turbulent trailing-edge separation prematurely in areas of large adverse pressure gradients, and was found to be very sensitive to inlet turbulence quantities. Despite these deficiencies, the model gave results that were much closer to wind-tunnel tests than those given by the fully turbulent k-ω shear stress transport model, which tended to underestimate downforce. Significant differences between the transitional and fully turbulent models in terms of pressure field, wake thickness and turbulent kinetic energy production were found and highlighted the importance of using transitional models for wings operating at low Reynolds numbers in ground effect. The k-kL-ω model has been shown to be appropriate for the simulation of separation-induced transition on a three-dimensional wing operating in ground effect at low Reynolds number.
Keywords: Boundary layer; turbulence; closure model; wind tunnel; laminar separation bubble; Reynolds number